Sull'uso delle pro-forme nelle riprese coreferenziali del testo - Gałkowski, Artur (Studia Romanica Posnaniensia, 2001)
The article takes up some aspects of the use of pronouns as referential pro-forms in the process of text substitution. - The main emphasis is placed on the distinction between anaphoric and cataphoric pronominalization and on their meaning in coreferential chains. The author states that pronominalization does not occur in all cricumstances but in some cases repetition, as a special kind of the pro-form, is used. The conclusion points out that pro-forms can be employed as long as they do not interfere with the continuity of topic and the cohesion of text.